10 steps every CISO should take to secure next-gen software - Blake, Cindy (O'Reilly Media, 2020)
As countless breaches have proved, application security is no longer optional. But most established and trusted app sec tools were developed 10-15 years ago for a different world of software development. The next generation of software brings a different set of risks that requires new processes to manage. This report examines the security implications involved in next-generation software, from the code itself to the methodologies by which it's developed and the infrastructure surrounding its use. Cindy Blake shows you what this new software landscape looks like, covering new and evolving development technologies, tools, and frameworks and why they're relevant to security. CISOs will see why cloud native and serverless architectures (for building software) and DevOps and Agile methodologies (for managing it) are critical areas for application security as they learn the 10 steps for securing next-generation software. Discover the DevOps principles that CISOs often overlook Explore three critical shifts of next-gen software and how they impact security Dive into a next-gen application security program Get practical advice for securing next generation software.